Gender, Ethnicity, and Class in Repressive Regimes: A Review of the Universe of Victims of the Last Military Dictatorship in Argentina Half a Century Later - Rodriguez Aguero, Laura (Hispania Nova, 2026)
Studies on Argentina’s last military dictatorship have seen enormous academic development. However, most have focused on urban subjects located in the center of the country. With the aim of making visible and problematizing the presence of victims rarely seen in academic research, this pa per aims to address the territorial configuration of dictatorial repressive networks from the perspective of gender, ethnicity, and class. In this regard, from an intersectional theoretical perspective and a "history from below" perspective, this paper analyzes the state repressive practices deployed against rural workers of Creole and Indigenous origins, as well as common criminals and prostitutes. On the other, we examine the class, gendered, and racialized nature of the scales and temporalities of local repressive networks. This approach will be based on oral sources of our own creation, period diaries, and information from the judicial system.